Catalytic partial oxidation of propylene to acrolein: the catalyst structure, reaction mechanisms and kinetics - Fansuri, Hamzah (Curtin University, 2005)
Bismuth molybdates have long been known as active catalysts for selective oxidation of olefins. There are several phases of bismuth molybdates but only three of them are known to be active for partial oxidation of propylene to acrolein, namely, α, β, and γ bismuth molybdates. A significant amount of work has been carried out and reported in the literature, aiming to understand the reaction mechanisms so as to control the reaction process. It has been revealed that the oxidation reaction follows the redox mechanisms and lattice oxygen plays a key role as the main oxygen source for the reaction and controls the catalyst performance. The properties of the lattice oxygen are influenced by the bulk crystalline structure of the catalyst. Therefore, it is possible that the crystal structure influences the performance of the catalyst in promoting the partial oxidation reaction. However, there appears to be a lack of detailed reports in the literature on the relationship between the bulk crystal structure and the activity and selectivity of the catalyst for the partial oxidation reaction. The work reported in this thesis has been designed to achieve an improved understanding of the catalyst structure in relation to the activity and selectivity of the catalyst for the partial oxidation of propylene to acrolein.In order to fulfil the objectives of this study, several investigation steps have been taken, namely 1) acquiring and analysing the catalyst structural parameters under real reaction conditions as well as at room temperature by means of neutron diffraction and X-ray diffraction, 2) obtaining kinetics from experimentation using a packed-bed reactor operating under differential reactor mode so as to eliminate the mass diffusion effect, and 3) developing and proposing reaction mechanisms which contain events that occur on the crystalline structure of the catalysts, particularly lattice oxygen, during the reaction. Characterisation of the structure of the catalysts has been carried out by means of In-situ neutron diffraction, which has the ability to probe the crystal structure at atomic level. The structure is characterised under simulated reaction conditions to investigate the dynamics of the crystal structure, particularly lattice oxygen, during the reaction. The In-situ diffraction studies have uncovered the relationship between the crystal structure of bismuth molybdates and their selectivity and activity towards the catalytic partial oxidation of propylene to acrolein. The possible active lattice oxygen in the bismuth molybdate structures has been identified. The active lattice oxygen ions are responsible for maintaining redox balance in the crystal lattice and thus control the catalyst activity and selectivity. Mobile oxygen ions in the three bismuth molybdate crystal phases are different. The mobile oxygen ions are O(1), O(11), and O(12) in the α phase; O(3), O(11), O(16), and O(18) in the β phase; and O(1) and O(5) in the γ phase.The mobile lattice oxygen ions are proposed to be the source of the oxidising oxygen responsible for the selective oxidation of propylene to acrolein. One common feature of all mobile oxygen ions, from a catalyst crystal structure point of view, is that they are all related to molybdenum ions rather than bismuth ions in the lattice. By modifying the physical and chemical environment of the molybdenum oxide polyhedra, it is possible to modify the catalyst selectivity and activity. The diffraction diagnoses have also shown that molybdenum oxide polyhedra in all bismuth molybdate are unsaturated. In contrast, the bismuth oxide polyhedra are over charged. The co-existence of molybdenum ions that are co-ordinately unsaturated with bismuth ions that are over valence-charged promote the formation of allyl radical such as those found in the partial oxidation of propylene to acrolein. The molybdenum ions become propylene-adsorbing sites while the bismuth ions are the active sites to attract hydrogen from the adsorbed propylene, leading to the formation of the allyl intermediate. Oxygen ions from the mobile lattice oxygen are a more moderate oxidant than molecular oxygen. With their mild activity, the partially oxidised products are the main products such as acrolein and formaldehyde when oxygen ions react with the allyl intermediate while more complete combustion products such as carbon oxides and organic acids become the side products.Investigation into the kinetics and reaction mechanisms has revealed the aforementioned evidence to support the role of the mobile lattice oxygen ions in the partial oxidation of propylene to acrolein. The kinetic experiments have employed the power rate law to model the kinetic data. The model shows that the reaction orders in propylene and oxygen concentrations are a function of the reaction temperature. The reaction order in propylene increases with reaction temperature, from 0.6 at 300°C to 1.0 at 450°C for all the bismuth molybdate catalysts, while the reaction order in oxygen decreases from 0.6 at 300°C to 0 at 450°C. The activation energies are 99.7, 173, and 97.7 kJ.mol-1 for α-Bi2Mo3O12, β-Bi2Mo2O9, and γ-Bi2MoO6, respectively. The changes in reaction orders with respect to propylene and oxygen indicate that the reaction occurs through the redox mechanisms, using the mobile lattice oxygen. The structural dynamics identified earlier explains the decrease in the acrolein selectivity at high temperatures (ca above 390°C). At these temperatures, the mobile oxygen becomes more mobile and more active. As a result, as the mobility of the oxygen ions increase, their reactivity also increases. The increase in the oxygen reactivity leads to unselective, complete oxidation reaction, forming the complete oxidation products CO2 and H2O. The reduction-reoxidation of bismuth molybdate is controlled by the diffusion of oxygen ions in the lattice, because the reduction sites do not have to be adjacent to the oxidation sites. The oxygen diffusion rate is in turn controlled by how mobile the lattice oxygen ions are.Hence, the mobile oxygen ions discussed earlier control the catalyst activity in catalysing the reaction of propylene partial oxidation. The examination of several reaction mechanism models has given further evidence that the propylene partial oxidation to acrolein occurs via the redox mechanism. In this mechanism, the rate of acrolein formation depends on the degree of fully oxidised sites in the bismuth molybdate. The oxidised sites affect the apparent reaction orders in propylene and oxygen and thus control the kinetics of partial oxidation of propylene to acrolein. The more easily the reduced catalysts are reoxidised, the more active the catalysts in converting propylene to acrolein. A set of reaction steps has been proposed, which adequately reassembles the reaction mechanism. Side product reactions are also identified and included in the mechanisms. The present thesis has revealed a much detailed insight into the role of lattice oxygen in the catalytic partial oxidation of propylene to acrolein over bismuth molybdates and established the relationship between structure and activity and selectivity of the catalyst. This work has laid a foundation for future catalyst design to be based on structural knowledge of the catalysts.